An den Grenzen des Waldes und der menschlichen Siedlung - Koch, Eva-Maria (Alpine Forschungsstelle Obergurgl, 2012)
The subalpine zone of the inner Oetz Valley (Obergurgl/Vent, Tyrol, Austria) was influenced by human activities since several thousands of years. As a consequence a high diversity of plant communities developed at formerly forested areas by stone pine (Pinus cembra). Book no. 2 of the Alpine Research Centre Obergurgl aims to highlight the ecology of these environments at the edge of human settlement in a comprehensive way. Descriptions of the plant communities as well as an overview on treeline research in Obergurgl and investigations on tree-ring series are among the main chapters of the book. Investigations of toponyms and archeological findings at the edge of human settlement are reported here in an exclusive way. A chapter on lithology concludes the volume.